1975
DOI: 10.1017/s0022112075000614
|View full text |Cite
|
Sign up to set email alerts
|

Hydromechanics of low-Reynolds-number flow. Part 2. Singularity method for Stokes flows

Abstract: The present study furthcr explores the fundamental singular solutions for Stokes flow that can be useful £or constructing solutions over a wide range of free-stream profiles and body shapes. The primary singularity is the Stokeslet, which is associatedwith a singular point force embedded in a Stokes flow. From its derivatives other fundamental singularities can be obtained, including rotlets, strcsslets, potential doublets and higher-order poles derived from them. For treating interior Stokes-flow problems new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
335
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(346 citation statements)
references
References 14 publications
8
335
0
3
Order By: Relevance
“…We consider the same prolate spheroid as in the previous example, and compute the swimming velocity U = Ux when two jets (with fluxes ±q) are placed at x = ±bx. The resistance problem has a tractable solution and representation using the singularity methods described by Chwang and Wu [46]. In that work it was shown that a prolate spheroid translating along its minor axis with velocityŨ =Ũx generates flow and pressure fields given by…”
Section: E Example 3: a Prolate Spheroid Translating Along Its Minormentioning
confidence: 99%
“…We consider the same prolate spheroid as in the previous example, and compute the swimming velocity U = Ux when two jets (with fluxes ±q) are placed at x = ±bx. The resistance problem has a tractable solution and representation using the singularity methods described by Chwang and Wu [46]. In that work it was shown that a prolate spheroid translating along its minor axis with velocityŨ =Ũx generates flow and pressure fields given by…”
Section: E Example 3: a Prolate Spheroid Translating Along Its Minormentioning
confidence: 99%
“…The cell body was modelled as a prolate ellipsoid, with a major axis (a), minor axis (b) and eccentricity (e), where e ¼ ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi ffi 1 À ðb 2 /a 2 Þ: p Using this approximation, the viscous drag and torque on the cell body can be calculated from the following equations [10,78]: and m is the viscosity of water. Equations (4.1a,b) govern the viscous drag of the body, whereas equation (4.1c) shows the relationship between the torque and rotation of a prolate ellipsoid around its minor axis.…”
Section: Modellingmentioning
confidence: 99%
“…Equations (4.1a,b) govern the viscous drag of the body, whereas equation (4.1c) shows the relationship between the torque and rotation of a prolate ellipsoid around its minor axis. Equations (4.1d,e) are the linear drag coefficients of a prolate ellipsoid, and equation (4.1f ) is the drag coefficient of rotation of a prolate ellipsoid around its minor axis [78]. The viscous drag (F G ) and net moment (M G ) on the body must be balanced by the fluid forces of the flagella (F f and M Gf ), as shown below: Considering that T. foetus has four flagella, the fluid forces and net moment generated from the flagella can be expanded to the To accurately derive the flagellar forces in the laboratory frame, the absolute velocity (laboratory frame of reference) was calculated from the following equation:…”
Section: Modellingmentioning
confidence: 99%
“…They generate eddies, thereby efficiently producing inertial thrust. Micron sized small swimmers lack these possibilities and must use nonreciprocal less efficient conformational dynamics [3][4][5][6]. Swimming strategies of low-Reynoldsnumber swimmers vary.…”
mentioning
confidence: 99%